2018
DOI: 10.1038/s41394-018-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a clinical implementation of a respiratory muscle training group during spinal cord injury rehabilitation

Abstract: Respiratory resistance training improved respiratory function of individuals with acute spinal cord injury. Even if the combined respiratory muscle training was performed with more repetitions per training and nearly twice as long, relative improvements of respiratory function parameters were comparable with isolated inspiratory muscle training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have focused more on muscle strength compared with muscle endurance. In a retrospective study by Raab et al, inspiratory or combined inspiratory and expiratory muscle training was performed in a group setting with respiratory function measurements before and after the training period (16). They found that the training improved respiratory functions, but the relative improvements in combined respiratory muscle training were comparable with isolated inspiratory muscle training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused more on muscle strength compared with muscle endurance. In a retrospective study by Raab et al, inspiratory or combined inspiratory and expiratory muscle training was performed in a group setting with respiratory function measurements before and after the training period (16). They found that the training improved respiratory functions, but the relative improvements in combined respiratory muscle training were comparable with isolated inspiratory muscle training.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66] RST increases inspiratory and expiratory pressure-generating capacity, vital capacity, and maximal voluntary ventilation in adults with SCI. [66][67][68] These gains in respiratory function help protect against potentially life-threatening complications like pneumonia. 69 Examples of RST include resistive training or threshold training for both inspiration and expiration (IMST/EMST) 67 and can successfully be implemented in rehabilitation settings.…”
Section: Training and Treatmentmentioning
confidence: 99%
“…76 These measures are reliable in the SCI population, 77 easy to perform, are relatively low-cost measures, and are necessary to perform regularly to adapt RST goals (Table 3). 68,78 Furthermore, quantitative measurement of respiratory function should be used to guide education needs, home exercise, monitoring frequency, and resource needs after discharge from inpatient rehabilitation. 68,78…”
Section: Quantitative Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The following examinations and assessments were identified as being performed insufficiently often [19] within the time frame recommended by the EMSCI [22] or by the clinic's internal recommendation list [14]: magnetic resonance imaging (MRI) and computed tomography (CT) of the spine during initial treatment (trauma protocol), recommended within eight days after newly acquired spinal cord injury [23]; manual muscle test of the lower extremity, recommended within 28 days after newly acquired spinal cord injury [24]; International Standards For Neurological Classification of Spinal Cord Injury (ISNCSCI), recommended either within eight days after admission to a specialised acute and rehabilitation clinic or within 40 days after newly acquired spinal cord injury [25][26][27]; electrophysiological evaluation of the lower extremity, recommended within 40 days after newly acquired spinal cord injury [28]; urodynamic testing, recommended within 84 days after newly acquired spinal cord injury [18]; and lung function testing, recommended within 40 days after newly acquired spinal cord injury [29].…”
Section: Assessmentsmentioning
confidence: 99%